Charged-Hadron Pseudorapidity Distributions in p-p and Pb-Pb Collisions at LHC Energies - Bao-Chun Li; Ya-Zhou Wang (Advances in High Energy Physics)
Pseudorapidity distributions of charged hadrons produced in p-p and Pb-Pb collisions at LHC energies were measured by the CMS and ALICE Collaborations, respectively. An improved Tsallis distribution in the two-cylinder model is used to describe the pseudorapidity spectra. We consider the rapidity shift at the longitudinal direction in the geometrical picture of the collisions. The calculated results are in agreement with the experimental data. The gap between the projectile cylinder and the target cylinder increases with the centralities. The rapidity shifts in the cylinders also increase with the centralities.